Throughput model of Wi-Fi cascading based on saturated TCP traffic - Junxiong ZHANG; Jianzhao LIU; Xiaohu GE; Weimin WU (物联网学报)
At present, the importance and commercial value of wireless fidelity (Wi-Fi) technology have been widely recognized.And people are also pursuing better quality of service (QoS).Transmission control protocol (TCP) as a connection-oriented communication protocol that provides end-to-end reliability services, its importance is also increasing, and it is the dominant transmission protocol in the Internet.Besides, since the coverage of a single access point (AP) is limited, it is often necessary to extend the coverage through cascading in many scenarios.However, the current research on cascading scenarios is based on the user datagram protocol (UDP), which means that only downlink traffic exists in the scenario.Actually, uplink and downlink traffic often exist at the same time in many scenarios, which means TCP traffic is running.How to calculate the TCP throughput obtained by users in the cascading scenario has always been an unresolved problem.To solve this problem, firstly, a Wi-Fi throughput model under the condition of saturated TCP traffic was established in the cascading scenario, and the calculation of user throughput was realized through two Markov chains.Secondly, a cascading system was built and actual tests were conducted.The validity of the model is verified by comparing the theoretical simulation results with the actual test results.